Moderate Physical Exercise Activates ATR2 Receptors, Improving Inflammation and Oxidative Stress in the Duodenum of 2K1C Hypertensive Rats - da Silva, Alda Cássia Alves; Severo, Juliana Soares; dos Santos, Brenda Lois Barros; Mendes, Pedro Henrique Moraes; Nobre, Lívia Maria Soares; de Oliveira, Ana Patrícia; Ferreira, Francisco Cleber Silva; Medeiros, Jand Venes Rolim; Lima-Junior, Roberto Cesar; Havt, Alexandre; Palheta-Junior, Raimundo Campos; dos Santos, Armênio Aguiar; et al. (Frontiers in Physiology, 2021)
Background: In addition to the cardiovascular and renal systems, the gastrointestinal tract also contains angiotensin ATR1a, ATR1b, and ATR2. We previously observed that the 2Kidney-1Clip hypertension model elicits physical exercise and gastrointestinal dysmotility, which is prevented by renin-angiotensin system blockers. Here we investigate the effect of physical exercise on inflammation, stress biomarkers, and angiotensin II receptors in the duodenum of 2K1C rats. Methods: Arterial hypertension was induced by the 2K-1C surgical model. The rats were allocated in Sham, 2K1C, or 2K1C+Exercise groups. One week after surgery, they were submitted to a physical exercise protocol (running 5x/week, 60min/day). Next, we assessed their intestinal contractility, cytokine levels (TNF-α, IL-1β, IL-6), oxidative stress levels (MPO, GSH, MDA, SOD), and the gene expression of angiotensin receptors (ATR1A, ATR1B, ATR2). Results: In comparison with the Sham group, the 2K1C arterial hypertension decreased (p<0.05) intestinal contractility. In comparison with 2K1C, the 2K1C+Exercise group exhibited lower (p<0.05) MPO activity (22.04±5.90 vs. 78.95±18.09 UMPO/mg tissue) and higher (p<0.05) GSH concentrations in intestinal tissues (67.63±7.85 vs. 31.85±5.90 mg NPSH /mg tissue). The 2K1C+Exercise group showed lower (p <0.05) cytokine levels in the intestine than in 2K1C rats. In comparison with the Sham group, the 2K1C+Exercise rats showed higher (p<0.05) gene expression of ATR2 in the duodenum. Conclusion: 2K-1C hypertension elicits an oxidative stress and inflammation process in the duodenum. Physical exercise modulates the expression twice as much of ATR2 receptors, suggesting possible anti-inflammatory and antioxidant effects induced by exercise.